2020
DOI: 10.3389/fmicb.2020.02069
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis and Functional Characterization Reveal the Duck Interferon Regulatory Factor 1 as an Important Restriction Factor in the Replication of Tembusu Virus

Abstract: Duck Tembusu virus (DTMUV) infection has caused great economic losses to the poultry industry in China, since its first discovery in 2010. Understanding of host anti-DTMUV responses, especially the innate immunity against DTMUV infection, would be essential for the prevention and control of this viral disease. In this study, transcriptomic analysis of duck embryonic fibroblasts (DEFs) infected with DTMUV reveals that several innate immunity-related pathways, including Toll-like, NOD-like, and retinoic acid-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…In the present study, MDA5 and IFN-β were found to be involved in the production of chCMPK2 upon virus infection. Our results were consistent with preliminary hypothesis on duck that CMPK2 may be induced through the IFNα/β signaling pathway ( Xiang et al, 2020 ). MDA5 and RIG-I, as members of the evolutionarily conserved RIG-like helicase family, play critical roles in the host antiviral defense against pathogens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, MDA5 and IFN-β were found to be involved in the production of chCMPK2 upon virus infection. Our results were consistent with preliminary hypothesis on duck that CMPK2 may be induced through the IFNα/β signaling pathway ( Xiang et al, 2020 ). MDA5 and RIG-I, as members of the evolutionarily conserved RIG-like helicase family, play critical roles in the host antiviral defense against pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…In the current report, we first demonstrated that chCMPK2 inhibited the propagation of AIV H9N2 in a dose-dependent way, and chCMPK2 may also be an antiviral molecule against NDV. CMPK2 has been reported to be able to inhibit viral and bacterial infection, including SVCV, Dengue virus (DENV), Duck Tembusu virus (DTMUV), HIV-1 and Aeromonas hydrophila CCL1 ( El-Diwany et al, 2018 ; Liu et al, 2019 ; Xiang et al, 2020 ; Feng et al, 2021 ; Lai et al, 2021 ). Our analysis indicated that overexpression of chCMPK2 in DF-1 cells significantly inhibited H9N2 NP expression at the mRNA and protein levels, and knockdown of chCMPK2 had the opposite effects, which suggested that chCMPK2 was an important antiviral factor against AIV.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous exploration, CMPK2 was upregulated in response to the LPS in macrophages [ 48 ] and various types of viruses [ 40 , 43 , 57 ]. Our RNA seq analysis in THP-1 and expression study in THP-1 cells and BMDMs showed LPS and Poly (I:C) dependent CMPK2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Duck OASL activates the OAS/RNaseL pathway (58). Similarly, overexpression of duck Viperin reduces viral replication (59).…”
Section: Discussionmentioning
confidence: 99%